1993
DOI: 10.1007/bf01297079
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of exogenous lactase (?-galactosidase) preparations onin vivo lactose digestion

Abstract: Microbial-derived beta-galactosidase (beta-gal) enzyme preparations improve in vivo lactose digestion and tolerance through enhanced gastrointestinal digestion of lactose. Three different beta-gal preparations, Lactogest (soft gel capsule), Lactaid (caplet), and DairyEase (chewable tablet) and placebo were fed to lactose maldigesters with either 20 g or 50 g of lactose to compare the efficacy of these products and to further establish a dose-response relationship for use. All enzyme preparations dramatically r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
3

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 10 publications
2
33
0
3
Order By: Relevance
“…Initially, this approach was judged as not practical because of the necessity to add the enzyme some hours before milk consumption (Rask Pedersen et al, 1982;Onwulata et al, 1989;Lin et al, 1993). Other studies, carried out to resolve this matter, have demonstrated the efficacy of the lactase also when added at mealtime (Solomons et al, 1985a, b;Barillas & Solomons, 1987;Corazza et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, this approach was judged as not practical because of the necessity to add the enzyme some hours before milk consumption (Rask Pedersen et al, 1982;Onwulata et al, 1989;Lin et al, 1993). Other studies, carried out to resolve this matter, have demonstrated the efficacy of the lactase also when added at mealtime (Solomons et al, 1985a, b;Barillas & Solomons, 1987;Corazza et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…However, this restriction leads to a reduction of intake of substances such as calcium, phosphorus and vitamins, and may associate with decreased bone mineral density (Solomons et al, 1985a, b;Di Stefano et al, 2002). To overcome these limits, in the last years, several approaches have been studied: drugs that increase contact time between enzyme and substrate, either delaying orocoecal transit (ie loperamide) (Szilagyi et al, 1996(Szilagyi et al, , 2000 or delaying gastric emptying (ie propantheline) (Peuhkuri et al, 1999); continuous lactose consumption to induce colonic adaptation (Briet et al, 1997); substitutes for milk (Swagerty et al, 2002); yogurt and probiotics for their bacterial bgalactosidase activity (Onwulata et al, 1989;Saltzman et al, 1999); addition of exogenous lactase to the milk before its consumption (Solomons et al, 1985a, b;Barillas & Solomons, 1987;Corazza et al, 1992;Lin et al, 1993). In particular, replacement therapy resulted in an efficacious strategy; nevertheless, only few double-blind and/or placebo-controlled trials have been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Digestive supplementation with exogenous lactase is the principal treatment for alleviating symptoms of lactose intolerance (2). Numerous clinical studies with such lactase supplements have reported largely limited success in treating this condition (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…This effect persists after the intervention is ceased [24]. Other probiotic strains have shown beneficial effects on lactose digestion and symptoms in lactase deficient persons [12,25,26]. Further investigation with different strains of bifidobacteria or lactobacilli on symptoms of lactose intolerance showed contradictory results.…”
Section: Removal Of Glucose and Galactosementioning
confidence: 97%